2013
DOI: 10.1016/j.ando.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonists or DPP-4 inhibitors: How to guide the clinician?

Abstract: RESUME :Le traitement pharmacologique du diabète de type 2 s'est enrichi, ces dernières années, de l'apport des médicaments à effet incrétine ciblant le glucagon-like peptide-1 (GLP-1). Ces médicaments comprennent soit des agonistes des récepteurs au GLP-1, à courte (injection 1 ou 2 x par jour : exénatide, liraglutide, lixisénatide) ou longue durée d'action (injection hebdomadaire : exénatide à libération prolongée, albiglutide, dulaglutide, taspoglutide) ; soit des agents inhibant l'enzyme inactivant le GLP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
0
8
0
2
Order By: Relevance
“…The beneficial glycemic level lowering effect of all GLP-1 RAs in our analysis was consistent with previous studies [ 10 , 121 ]. Scheen’s [ 122 ] study reported that the HbA1c lowering potential for GLP-1 RAs is approximately at 1%–1.5% on average. A review of 8 head-to-head phase III clinical programs showed that the primary efficacy endpoint in all of the GLP-1 RAs was change in HbA1c from baseline with a noninferiority margin of 0.4%[ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial glycemic level lowering effect of all GLP-1 RAs in our analysis was consistent with previous studies [ 10 , 121 ]. Scheen’s [ 122 ] study reported that the HbA1c lowering potential for GLP-1 RAs is approximately at 1%–1.5% on average. A review of 8 head-to-head phase III clinical programs showed that the primary efficacy endpoint in all of the GLP-1 RAs was change in HbA1c from baseline with a noninferiority margin of 0.4%[ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although both GLP-1 analogs and DPP-4 inhibitors have similar pharmacological approaches, their routes of administration (subcutaneous versus oral) differ considerably [Scheen, 2013]. Furthermore, physicians may guide the pharmacological choice of treatment based on the clinical characteristics of patients with diabetes, drug safety profile, therapeutic goals, and patient preference [Inzucchi, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Incretin-based therapies such as dipeptidyl peptidase-4 (DPP-4) inhibitors or glucagon-like peptide-1 (GLP-1) analogs increase plasma concentrations of active GLP-1 and exert antihyperglycemic effects in a glucose-dependent manner [Scheen, 2013]. Although these therapies are safe and effective in lowering hemoglobin A1c (HbA 1c ) without the risk of hypoglycemia and weight gain, they vary in administration route, efficacy, and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 effects include increased insulin secretion, decreased glucagon release, increased satiety and slowed gastric emptying 4. The most common adverse reactions to dulaglutide reported in 5% or more of patients include nausea, diarrhoea, vomiting, abdominal pain, decreased appetite, dyspepsia and fatigue 5 6.…”
Section: Discussionmentioning
confidence: 99%